Removal of carbamazepine (CBZ) from synthetic urine by FeOCl-coated ceramic membrane: The study of kinetic modeling. (July 2022) - Yao, Hong; Zhang, Xu; Liu, Fang; Sun, Shaobin
Abstract: Pharmaceuticals residual in the human urine are difficult to remove in the conventional wastewater treatment plants (WWTPs) and cause a serious environmental issue. Hence, we developed a FeOCl-coated ceramic membrane coupled with the Photo-Fenton system for direct removing pharmaceuticals from human urine. In this study, the removal efficiency of CBZ from hydrolyzed urine was higher than that from fresh urine. The apparent rate constant ( k obs ) of CBZ from hydrolyzed urine could reach 0.0163 min −1, 1.39 times higher than that from fresh urine (0.0117 min −1 ). Interestingly, this performance was not caused by the solution pH. The effect of substrates in the hydrolyzed urine was further explored, verifying that ammonia played a key role in quenching the hydroxyl radicals ( OH). The nitrogen reactive species (RNS) were then generated, resulting in that the k obs of CBZ from hydrolyzed urine sharply decreased, compared with the phosphate buffer solution (pH = 9). The quenching experiment was further to confirm that the RNS was primary reactive oxide species in the hydrolyzed urine. Based on the data of kinetic study and reported previously, competitive kinetic modeling was set up, which could successfully predict the removal efficiency of pharmaceuticals from hydrolyzed urine. The study provided a new method for removing pharmaceuticals residual in human urine and the kinetic modeling could be widely used to predict the removal of pharmaceuticals from human urine. Graphical abstract: Image 1 Highlights: FeOCl-coated ceramic membrane could be used to efficiency remove antibiotics from human urine. . FeOCl-coated ceramic membrane showed better performance in hydrolysis urine than fresh urine. Reactive nitrogen species played a key role in the removal of antibiotics from hydrolysis urine. Competitive kinetic modeling could accuracy predict the removal efficiency of antibiotics from hydrolysis urine.